Role of Parents in Fostering the Practice of Physical Exercise and Activities - Hutkemri Zulnaidi, Syed Kamaruzaman Syed Ali, Tan Pei Chian, (Opción, 2019)
This study aims to identify the role of parents in fostering physical exercise and activities amongst children via descriptive and inference statistics. Descriptive statistics included the use of percentage, mean and standard deviation. By contrast, inference statistics involved the use of t-test and one-way ANOVA. Results show a substantial difference in the role of parents in fostering the practice of physical exercise and activities based on race and academic qualification. In conclusion, parents should play a significant role in fostering the practice of a healthy lifestyle amongst their children, in which race is immaterial but the fostering applies to parents.